Efficient Adsorption of Cr(VI) from Aqueous Solutions Using Composites Modified with Ni/Al LDH and Keggin Type Compounds - Normah, Normah; Adhiyanti, Nurmalina; Sayeri, Rabellia Juladika; Wijaya, Alfan (Indonesian Journal of Material Research, 2024)
This study aims to synthesize the NiAl-LDH/K4[α-SiW12O40] composite using the coprecipitation method and evaluate its ability to adsorb Cr(VI) from aqueous solutions. The material characterization showed a significant increase in the specific surface area of the composite compared to pure NiAl-LDH, contributing to an enhanced Cr(VI) adsorption capacity. XRD and FT-IR results confirmed the successful synthesis and integration of K4[????-SiW12O40] into the NiAl-LDH structure. At the same time, BET analysis indicated that the specific surface area of the composite doubled compared to pure NiAl-LDH. The adsorption kinetics data indicated that the adsorption process followed the Pseudo-Second-Order (PSO) model with an R2 value close to 1, suggesting the dominance of chemisorption in the Cr(VI) adsorption mechanism. Isotherm analysis showed that the Freundlich model was more suitable than the Langmuir model, indicating that adsorption occurred on a heterogeneous surface with multilayer formation. The Cr(VI) adsorption capacity of the NiAl-LDH/K4[α-SiW12O40] composite reached 17.123 mg/g, higher than that of pure NiAl-LDH at 188.68 mg/g. The Cr(VI) adsorption process involved chemical interactions between Cr(VI) and functional groups on the adsorbent surface, complex formation, and precipitation.